Nitrite and thiocyanate in the fasting and secreting stomach and in saliva. Issue 1 (January 1977) - Ruddell, W S; Blendis, L M; Walters, C L
Abstract : The concentrations of nitrite and thiocyanate in fasting and pentagastrin stimulated gastric juice and in saliva have been examined. Nitrite was found in all of 17 samples of fasting gastric juice, mean 4-9 +/- 1-1 muM. Stimulation of gastric secretion with pentagastrin caused no significant change in nitrite concentration. Thiocyanate was detected in all of 21 samples of fasting gastric juice and the difference in concentration between smokers and non-smokers probably reflects similar differences in saliva. In contrast to the nitrite data there was a significant drop in thiocyanate concentration of gastric juice after pentagastrin from 0-9 +/- 0-1 mM to 0-3 +/- 0-04 mM, suggesting a salivary origin for the thiocyanate in gastric juice. Thiocyanate is a powerful catalyst of nitrosation, which, together with small amounts of nitrite and naturally occurring amines could lead to the intragastric formation of carcinogenic nitrosamines and in certain circumstances be a factor in the aetiology of gastric cancer.